Budget forecast errors in Spanish municipalities: The role of transparency - Israel García (Philipps-University Marburg, School of Business and Economics, 2023)
Does budget transparency effectively limit the use of creative accounting to circumvent fiscal rules? Through examining a Spanish reform that limited the obligation to provide regular budget information, I study the effect of relaxing transparency rules on budget forecast errors. After the reform, municipalities with less than 5,000 inhabitants were not obligated to provide quarterly information on cumulative budget execution and forecast deviations. Using a difference-in-differences estimator in a sample of municipalities from this Madrid region between 2010-2019, I compare expenditure and revenue forecast errors between municipalities below 5,000 inhabitants (treatment group) and above 5,000 inhabitants (control group). I observe that reducing the frequency of budget reporting leads to a systematic underestimation of planned expenditures and revenues. Furthermore, most differences are found in pre- and electoral periods, indicating a political forecast cycle. I then combine the introduction of a gender quota with the transparency reform to study gender differences in budget forecast errors, finding that female politicians systematically deviate from initial expenditure projections for electoral purposes.
Keywords: C23; E62; D72; H68; J16; 330; Budget transparency; Fiscal rules; Difference-in-differences; Political forecast cycles; Gender; Spanish municipalities; Madrid region